Impacts of winter climate change on northern forest understory carbon dioxide exchange determined by reindeer grazing - Kantola, Noora; Welker, Jeffrey M.; Leffler, A. Joshua; Lämsä, Juho; Paavola, Riku; Suominen, Otso; Väisänen, Maria (Elsevier BV, 2025)
In northern regions, the ongoing climate change is altering snow depth with complex consequences for carbon dioxide (CO2) exchange and thus, global carbon (C) balance. In addition, ungulate grazers such as reindeer and caribou often alter plant and soil properties that may lead to modifications in the magnitudes and patterns of CO2 exchange. To understand how reindeer grazing, coupled with changes in snow depth affects CO2 exchange, we used recent snow treatments (ambient, reduced, and increased snow depth) combined with 25- and 55-year-old reindeer exclusions and the adjacent grazed areas in boreal and subarctic Scots pine forests that are main winter pastures for reindeer/caribou and cover a significant portion of boreal and subarctic landscapes. At both study sites, we measured understory net ecosystem exchange (i.e., NEE), ecosystem respiration (i.e., ER), and gross ecosystem production (i.e., GEP) over two snow-free seasons. We found that 55 years of reindeer exclusion increased C source strength by 136 % under ambient snow depth and 205 % under reduced snow depth in comparison to the grazed area with respective snow conditions. On the contrary, increased snow depth decreased C source strength inside the exclusion offsetting the difference between reindeer grazing treatments. Our results show that grazing may enhance ecosystem stability to winter climate change in comparison to long-term absence of grazing. This highlights the complexity of climate-grazer interactions in functioning of northern ecosystems which are experiencing variations in snow depth.